ISSUES OF THE INFLUENCE OF KARATE TRAINING ON WOMEN'S HEALTH - Dilnoza Artikbaeva (International Journal of Literature and Language Studies, 2026)
Abstract: In the context of modern hypodynamics and high levels of stress, finding effective forms of physical recreation for women is a priority task for sports science. Karate is a complex system that combines aerobic-anaerobic loads and psychophysical regulation, but the gender aspects of its impact on the body have not been sufficiently studied. The study utilized an analysis of scientific and methodological literature, methods for assessing physical fitness, the functional state of the cardiovascular system, and psychological questionnaires.